Viral Humanitarian Imagery: The Impact of #AllEyesonRafah on Global Social Media Dynamics - Luhuringbudi, Teguh; Liza, Fitri; Kurniawan, Edi; Masuwd, Mowafg Abrahem; Alrumayh, Safa Husayn (Kalijaga Journal of Communication, 2025)
This study examines the impact of viral humanitarian imagery, focusing on the AI-generated image campaign with the hashtag #AllEyesonRafah on global social media dynamics. It explores how the imagery influences public awareness and encourages responses to humanitarian issues in Rafah, Palestine. The study aims to identify a pattern linking social media use to social mobilization driven by humanitarian imagery. Data were collected through analysis of digital content posted by public figures and humanitarian organizations, employing a qualitative approach informed by relevant communication theories. Primary sources included posts by public figures such as Bella Hadid, Ariana Grande, and Paramore, which significantly increased engagement. The analysis integrates three theories: Mark Granovetter’s Social Network Theory to examine the viral spread of AI-generated imagery on platforms like X, Instagram, and TikTok; Stuart Hall’s Representation Theory to analyze global public interpretations of these images; and Marshall McLuhan’s “Medium is the Message” Theory to assess how social media platforms and visual formats shape perception of the Rafah crisis. Findings indicate that viral humanitarian imagery not only raises awareness but also drives tangible global audiences. The study confirms social media’s role as an agent of social change, with its novelty lying in the detailed explanation of emotions in visual communication. The limitations of this study include the focus on one aspect of social media and the lack of longitudinal analysis, while suggestions for further research include a broader exploration of audience interactions and offline dimensions of similar phenomena.